Investigating the mutual effects of mobile phone use and civic culture: A systems approach - Hosseini, Seyed Hossein; Alavi, Seyed Maziar; Hosseini, Ali; Mehrjardi, Abolfazl Zare (UI Scholars Hub, 2022)
The extensive use of mobile phones has created the potential for promoting the culture and lifestyle of society. This study was conducted in Tehran; it examines the relationship between mobile phone use and civic culture. Considering the effect of multiple factors and complex relationships between variables, the study employs a systems approach to investigate the mutual relationship between mobile phone use and civic culture. Analysis utilized causal loop diagrams to depict relationships among variables, where 10 key factors were identified using the decision making trial and evaluation technique. These factors have exerted the greatest impact on civic culture; therefore, focusing on these factors during the urban policy-making process leads to the most effective policy that uses the least resources and budget. The ideal level of urban norms in the family was recognized as the most important influential and key factor followed by that at the community level of community acceptance in using the e-services of the city exerted the greatest impact on the issues. The outcomes could be used as a basis for policymaking in developing countries that intend to use mobile phones as a tool for promoting civic culture.